2005
DOI: 10.1104/pp.105.068437
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Bicarbonate Is Not the Substrate in Photosynthetic Oxygen Evolution

Abstract: (J.C., W.J.); and Max-PlanckInstitut fü r Bioanorganische Chemie, 45470 Muelheim an der Ruhr, Germany (K.B., J.M.)It is widely accepted that the oxygen produced by photosystem II of cyanobacteria, algae, and plants is derived from water. Earlier proposals that bicarbonate may serve as substrate or catalytic intermediate are almost forgotten, though not rigorously disproved. These latter proposals imply that CO 2 is an intermediate product of oxygen production in addition to O 2 . In this work, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 43 publications
3
42
0
Order By: Relevance
“…Despite numerous experiments this point remained unresolved (21,22,35,38). Although PSII membranes isolated from spinach also possess some carbonic anhydrase activity (6,8), there is presently no evidence for a carbonic anhydrase directly connected to higher-plant PSII, and there is also no need for a CCM function (discussed above). Our finding that under continuous illumination the activity of PSII is nevertheless dependent on the HCO − 3 concentration of the buffer therefore demonstrates that HCO − 3 directly affects the activity of PSII.…”
Section: Discussion Hco −mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite numerous experiments this point remained unresolved (21,22,35,38). Although PSII membranes isolated from spinach also possess some carbonic anhydrase activity (6,8), there is presently no evidence for a carbonic anhydrase directly connected to higher-plant PSII, and there is also no need for a CCM function (discussed above). Our finding that under continuous illumination the activity of PSII is nevertheless dependent on the HCO − 3 concentration of the buffer therefore demonstrates that HCO − 3 directly affects the activity of PSII.…”
Section: Discussion Hco −mentioning
confidence: 99%
“…The possible roles of inorganic carbon, C i ðC i = CO 2 ; H 2 CO 3 ; HCO − 3 ; CO 2− 3 Þ, in this process have been a controversial issue ever since Otto Warburg and Günter Krippahl (5) reported in 1958 that oxygen evolution by PSII strictly depends on CO 2 and therefore has to be based on the photolysis of H 2 CO 3 ("Kohlensäure") and not of water. These first experiments were indirect and, as became apparent later, were wrongly interpreted (6)(7)(8). Several research groups followed up on these initial results and identified two possible sites of C i interaction within PSII (reviewed in refs.…”
mentioning
confidence: 99%
“…This value is then compared to the uncatalyzed rate in the same assay solution. The first-order rate constants extracted from the time courses of the isotopic equilibration reactions are a highly sensitive approach for relative estimations of CA activities in different samples, as well as for comparison with the uncatalyzed (background) isotopic equilibrium (Tu et al, 1986;Clausen et al, 2005).…”
Section: A Disulphide Bond Between Cys-90 and Cys-258 Is Required Formentioning
confidence: 99%
“…On the basis of EXAFS measurements on Br K substituted samples, it was recently suggested that Cl K is not a direct ligand of the Mn 4 cluster in the S 1 state (Haumann et al 2006). In contrast to Cl K , no sound evidence exists for HCO 3 K binding within the WOC, and it is also highly controversial what kind of role it may play during photosynthetic water oxidation (Klimov & Baranov 2001;Stemler 2002;Clausen et al 2005;Hillier et al 2006). EXAFS on solution samples does not allow extracting the orientations of the Mn-Mn and MnCa vectors.…”
Section: Introductionmentioning
confidence: 99%